Hawaiian Legends of the Guardian Spirits - Loebel-Fried, Caren (University of Hawaii Press, 2002)
Ancient Hawaiians lived in a world where all of nature was alive with the spirits of their ancestors. These aumakua have lived on through the ages as family guardians and take on many natural forms, thus linking many Hawaiians to the animals, plants, and natural phenomena of their island home. Individuals have a reciprocal relationship with their guardian spirits and offer worship and sacrifice in return for protection, inspiration, and guidance. Hawaiian Legends of the Guardian Spirits is told in words and pictures by award-winning artist Caren Loebel-Fried. The ancient legends are brought to life in sixty beautiful block prints, many vibrantly colored, and narrated in a lively "read-aloud" style, just as storytellers of old may have told them hundreds of years ago. Notes are included, reflecting the careful and extensive research done for this volume at the Bishop Museum Library and Archives in Honolulu and at the American Museum of Natural History in New York. A short section on the process of creating the block prints that illustrate the book is also included. The matching poster of "A Chance Meeting with the Iiwi" measures 22 x 28 inches.